Application of Resampling and Boosting Methods Using the C5.0 Algorithm : Case Study Indonesia Family Survey Data - Hedi Kuswanto; Nurtiti Sunusi; Siswanto Siswanto; Nirwan Nirwan (Politeknik Statistika STIS, 2021)
Hypertension is a non-communicable disease that is characterized by an increase in systolic and diastolic blood pressure of more than 140 mmHg and or 90 mmHg. Hypertension needs to get more attention the condition is because hypertension will cause complications in the target organs and this disease does not appear to show significant symptoms at the beginning of the disease because it is called